Cognitive behavioral therapy for the treatment of chronic pelvic pain. Issue 3 (September 2020) - Urits, Ivan; Callan, Jessica; Moore, Warner C.; Fuller, Mitchell C.; Renschler, Jordan S.; Fisher, Paul; Jung, Jai Won; Hasoon, Jamal; Eskander, Jonathan; Kaye, Alan D.; Viswanath, Omar
Abstract : Chronic pelvic pain (CPP) in women is defined as noncyclical and persistent pain lasting more than six months perceived to be related to the pelvis. There are many etiologies that can cause CPP, including gynecologic, urologic, gastrointestinal, musculoskeletal, neurologic, and psychosocial. There is a strong association between psychological factors and CPP. It has been noted that almost half of women being treated for CPP report a history of sexual, physical, or emotional trauma. Women with CPP have been noted to have higher rates of psychological disorders in comparison to their peers. For men, the most common etiology for CPP is chronic prostatitis and there are also correlations with psychological disorders. There are many different treatment options for CPP: surgical, pharmacological, and non-pharmacological (alternative therapies). Cognitive-behavioral therapy may be another option when treating chronic pelvic pain syndrome and should be considered.